Management of Problematic Receivables in Islamic Banks: Monitoring, Strategies, and Risk Mitigation - Ulhaq, Faris Zia; Kurniawan, Kurniawan; Sobana, Dadang Husen (Institute Of Advanced Knowledge and Science, 2024)
This study examines the management of problematic receivables in Islamic banks, focusing on monitoring mechanisms, resolution strategies, and risk mitigation. The high Non-Performing Financing (NPF) ratio poses a significant challenge to Islamic banks, threatening their liquidity and reputation. This study evaluates the effectiveness of categorizing problematic receivables, from performing to non-performing financing. The findings indicate that rescue and resolution strategies can effectively reduce the NPF ratio. A case study of PT BPRS Harta Insan Karimah Parahyangan revealed that in 2023, the gross NPF ratio was 1.92%, and the net NPF ratio was 1.50%. Measures to further minimize the NPF ratio include: monitoring financing in the performing category and deposit funds, implementing rescue and resolution steps for problematic receivables, enhancing financing expansion with prudential principles, establishing Allowance for Earning Assets Losses (PPAP), and write-offs. Risk mitigation for problematic receivables can be carried out through.